SISTEM APLIKASI ANDROID PENCARIAN MULTI TEKS PADA TUJUH KITAB HADIS MENGGUNAKAN ALGORITME KNUTH-MORRIS-PRATT - Muhadir Muhammad Buguh Wawai; Dwi Sakethi (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Hadith according to Ibnu Taimiyah is something that comes from the Prophet Shallallahu ‘Alaihi wa Sallam which consists of words, deeds and taqrir. With the increasingly rapid development of information technology in today's world, Muslims can use it to study various sciences, including knowing the meaning of the contents of the hadith for guidance in daily life. One way that can make it easier is to use an Android-based application. In previous research, the multi-text search system on seven hadith books can search for hadiths from seven hadith books and is equipped with the Correct Spelling feature. However, the system that has been developed can only be accessed using a web browser, so the authors developed a multi-text search system on the seven hadith books based on Android to increase user interaction with the search system for the seven hadith books. The research stages used the Waterfall Method because the stages of the work were coherent. The hadith data used in the study were 52,618 hadiths in the database. Making system design using Unified Modeling Language modeling. The coding is done using the PHP and Java programming languages by applying the Knuth-Morris- Pratt Algorithm. Testing using Black Box Testing is a test whose testing process is derived from the program or component specifications. This Android-based system provides a better experience to users with an attractive appearance. The search results in the system use keyword weighting in the hadiths that are searched. Based on the results of the system development research, it was concluded that the multi-text search system on seven hadith books based on Android has been successfully developed and the results of testing the hadith search feature using categories make the search for hadiths more efficient.